(untitled) (Revista de Artes Marciales Asiáticas, 2023)
The purpose of the current study was to investigate the development of a woman Brazilian taekwondo expert coach. Based on the literature, a semi-structured interview on the coach development was used for the data collection, which was analyzed according to the content analysis method with a deductive approach. In addition, other relevant themes about the development of the woman coach emerged inductively during the data analysis. The results showed different variables that contributed to the coach development, such as personal characteristics, formal learning, non-formal learning, informal learning and positive support from family and friends. The influence of her career as a high-performance athlete stands out, as well as the knowledge of the English language, which contributed and facilitated the woman coach’s performance during international competitions. In conclusion, the present study provides valuable information about the shortage of expert woman coaches in Brazilian taekwondo, which may have significant implications for the taekwondo development and for the promotion of gender equality in the sport.